Improving Students’ Reading Comprehension Through Internet-Sourced Reading Materials As English Teaching Media - Faizal Yusa Erwinda; Ashari Ashari; Erna Wardani; Mustasyfa Thabib Kariad (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
The main concern of this research is improving students’ reading comprehension through internet-sourced reading materials as English teaching media. This research was intended to find out whether internet-sourced reading materials as English teaching media could improve students’ reading comprehension significantly in online teaching during COVID-19 Pandemic of 2020. The data were collected through pre-test and post-test results (quantitative) and Interview as well as observation (qualitative). The researcher conducts 7 meetings for pre-test, treatment and then post-test for both of experimental and controlled class. The research methodology was quasi-experimental research design with pre-test and post-test experimental. The subjects of this research were 20 students of 8B and 8C at SMP Gunungjati I Purwokerto. The subject of this research then divided into two classes, experimental and controlled class. The results of this research showed that internet-sourced reading materials for online English teaching could improve students’ reading comprehension, and improve students reading comprehension significantly. It is further proved with the Wilcoxon test result. Wilcoxon test result on experimental class (Asymp.Sig value 0.016, if the Asymp.Sig value was lower than 0.05 then H1 was accepted) which showed that experimental class students’ reading comprehension were improved. Furthermore, the research showed that students’ reading comprehension was improved significantly. It is proved through Mann-Whitney test result of both experimental and controlled class. The result of Mann-Whitney test (Asymp.Sig value 0.046 if the Asymp.Sig value was lower than 0.05 then H2 was accepted) which showed that students from experimental class test has significant improvement of reading comprehension when compared with controlled class. This result also supported by interview with the teacher, as well as through observation of students’ activity. Keywords: Reading, Reading Comprehension, English Teaching Media, Internet-sourced Reading Materials